Evaluating the utility of the HAS‐BLED bleeding‐estimator tool for transurethral resection of prostate - Lu Yu Kuo; Zhong Li Titus Lim; Caitlin Letch; Joshua Silverman; Jason Jae Yeun Kim; Scott McClintock (BJUI Compass)
Abstract Objectives To evaluate the utility of the HAS‐BLED bleeding risk‐estimation tool to predict for clinically significant postoperative haematuria in patients receiving transurethral resection of prostate (TURP). Patients and Methods A single‐centre, retrospective cohort analysis of patients underwent TURP from April 2019 to December 2023 for treatment of symptomatic benign prostate hyperplasia. The primary objective was to evaluate reliability of HAS‐BLED score in predicting postoperative bleeding event. A focus sub‐analysis was performed on anticoagulated patient cohort. Each patient was categorised in to HASBLED low‐, moderate‐ and high‐risk group according to the preestablished estimator tool. Patients' demographics, clinical, pathological and operative details were collected. Events of clinically significant haematuria within 3 months postoperatively were captured. Cohort characteristics and outcome were analysed with two‐sided t test and ANOVA test. Further weight‐adjusted multivariable analysis and ROC curve was performed to evaluate the predictive value of HAS‐BLED score. Results Our analysis showed that patients assigned as high‐risk by HAS‐BLED were at 2.17‐times higher chance of developing clinically significant haematuria compared to the low‐risk patients. The risk for high‐risk patient was 18.5% (95%CI 11.7–25.3%) and 8.5% (95%CI 4.6–12.4%) for low‐risk patients. Moderate‐risk did not demonstrate any significant difference relative to the low‐risk group. Sub‐analysis of 113 patients receiving long‐term anticoagulation accentuates the utility of the tool. The risk of haematuria for high‐risk patient was 32.7% (95%CI 20.7–44.7%), moderate‐risk patient was 28.7% (95%CI 17.0–40.3%), and low‐risk patient was 9.7% (95%CI 4.2–15.2%). In this cohort, the risk of haematuria was 3.37 and 2.96 times higher in the high and moderate‐risk compared to the low‐risk group, respectively. Conclusion This is the first study to validate a bleeding estimator tool for TURP patients. High HAS‐BLED score positively predicts clinically significant post‐TURP haematuria, particularly for patients receiving anticoagulation therapy.